De la premonición a la Acción Aportes del Maestro Francisco Emerson Castañeda Ramírez, al proyecto Cultural de la Universidad del Valle, en la consolidación del Grupo de Música y Danza Folclórica “Carmen López” en el periodo comprendido entre 1984 y el 2021 - Castañeda Ramírez, Francisco Emerson (Universidad Antonio Nariño, 2022)
In this degree work, the life story of Master Francisco Emerson Castañeda Ramírez is documented, from his birth, passing briefly through the different stages of his life, focusing on the stage of his relationship with the University of Valle where he develops the roles as a student, dancer, choreographer, director, cultural manager and teacher; he's contributions from each of these roles to the institution and in particular, to the University cultural project and the consolidation of the "Carmen López" Folk Music and Dance Group in the period between 1984 and 2021. This degree work uses as a methodology the story of life armed or edited, using the type of cross story, explanatory, with a qualitative approach.